THE RELATIONSHIP BETWEEN SMOKING AND ALCOHOL CONSUMPTION WITH BLOOD PRESSURE IN THE WORKING AREA OF THE SEI LANGKAI COMMUNITY HEALTH CENTER - Harefa, Priska Putri Meldawan; Desy, Desy; Eltrikanawati, T. Eltrikanawati (Jurnal Keperawatan Sriwijaya, 2026)
Aim: One of the main problems in adulthood is the high rate of hypertension which is now the number one cause of death in the world. This study aims to determine the Relationship of Smoking Behavior and Alcohol Consumption with Blood Pressure in Adult Hypertension Patients in the working area of the Sei Langkai Community Health Center, Batam City 2025. Method: This study used a quantitative method with a cross-sectional analytical design. The sample consisted of 80 respondents aged 30-45 years who were selected through a purposive sampling technique. Data were collected using questionnaires and sphygmomanometers, then analyzed using the chi-square test. Results: The results showed that smoking behavior had a significant relationship with hypertension (p = 0.001). Alcohol consumption also showed a significant relationship (p = 0.001). Conclusion: The conclusion of this study is that there is a strong and significant relationship between smoking behavior and alcohol consumption with blood pressure in adult hypertension patients in the study area.